1999
DOI: 10.1046/j.1365-2699.1999.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

The distance decay of similarity in biogeography and ecology

Abstract: Aim Our aim was to understand how similarity changes with distance in biological communities, to use the distance decay perspective as quantitative technique to describe biogeographic pattern, and to explore whether growth form, dispersal type, rarity, or support affected the rate of distance decay in similarity.Location North American spruce-fir forests, Appalachian montane spruce-fir forests. MethodsWe estimated rates of distance decay through regression of log-transformed compositional similarity against di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

93
1,643
9
38

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,553 publications
(1,804 citation statements)
references
References 53 publications
93
1,643
9
38
Order By: Relevance
“…Com o aumento da distância há um decréscimo na similaridade ambiental entre locais, formando gradientes de condições ambientais (Nekola & White 1999). Nestes casos as comunidades são estruturadas pelo nicho, e a distribuição das espécies de plantas está relacionada à distribuição heterogênea dos fatores ambientais no espaço (Pyke et al 2001;Zumquim 2007).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Com o aumento da distância há um decréscimo na similaridade ambiental entre locais, formando gradientes de condições ambientais (Nekola & White 1999). Nestes casos as comunidades são estruturadas pelo nicho, e a distribuição das espécies de plantas está relacionada à distribuição heterogênea dos fatores ambientais no espaço (Pyke et al 2001;Zumquim 2007).…”
Section: Introductionunclassified
“…As florestas tropicais, especialmente a Amazônia, são caracterizadas pela alta riqueza de espécies e baixa similaridade de espécies entre locais, tanto em escala local como em escalas regionais (Nekola & White 1999;Tuomisto et al 2003), sendo isto associado ao pequeno número de espécies comuns entre locais. A diferença na riqueza e composição de espécies entre locais é atribuída à diversidade beta, resultante da heterogeneidade de habitats e da limitação de dispersão das espécies (Ter Steege et al 2000;Tuomisto et al 2003;Costa et al 2005).…”
Section: Introductionunclassified
“…Accordingly, several studies have demonstrated a host of different factors that may influence variation of species composition through space: (1) spatial and environmental gradients (e.g. Clark et al, 1999;Nekola & White, 1999;Oliveira-Filho & Fontes, 2000;Carneiro & Valeriano, 2003;Steinitz et al, 2006Steinitz et al, , 2007bLegendre et al, 2009); (2) differences in the physiology, in the degree of biological interactions and in the dispersal ability of the species (Nekola & White, 1999;Tuomisto et al, 2003;Gilbert & Lechowicz, 2004); (3) barriers imposed by the configuration of the landscape and the influence of weather on species' dispersion (Nekola & White, 1999;Hubbel, 2001); (4) stochastic processes generated randomly and independently of environmental dissimilarities (Neutral Theory sensu Hubbel, 2001;Soininen et al, 2007b;Steinbauer et al, 2012); (5) species' tolerance to fragmentation (Arroyo-Rodríguez et al, 2013); (6) spatial scale (extension, resolution; Nekola & White, 1999;Steinitz et al, 2006;Soininen et al, 2007b;Arroyo-Rodríguez et al, 2013). Therefore, more accurate analysis involving other variables could yield further explanations regarding the spatial distribution observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Those processes normally produce an inverse relationship between similarity in species composition and geographical distance among sampling units (Nekola & White, 1999;Hubbel, 2001). Such relation is partially due to the spatial autocorrelation pattern of environmental variables, with closer locations tending to be more environmentally similar to each other (Legendre, 1993), which, by itself, influences the composition of species communities (Harrison et al, 1992;Jiménez-Valverde et al, 2010).…”
Section: Palavras-chavementioning
confidence: 99%
“…Area-and species-dependent extinction rates have been suggested to play important roles for species richness of oceanic islands (MacArthur & Wilson, 1967), species composition structure (Nekola & White, 1999) and nestedness in land-bridge islands and in habitat fragments (Patterson & Atmar, 1986;Cutler, 1991;Simberloff & Martin, 1991;Wright et al, 1998). Also, differential immigration may be important in producing nestedness (Simberloff & Martin, 1991;Kadmon & Pulliam, 1993).…”
Section: Data Setmentioning
confidence: 99%